KM3NeT underwater autonomous power supply system. (13th October 2021) - Leonora, E.; Longhitano, F.; Orlando, A.; Randazzo, N.; Riccobene, G.; Viola, S.
Abstract: The KM3NeT Collaboration aims to build in the depths of the Mediterranean Sea a neutrino telescope that consists of a kilometer-cube grid of photosensors encapsulated into transparent pressure resistant glass spheres. A crucial component of the detector is the acoustic positioning system, which provides the position of photodetectors and structures in the deep sea with an accuracy of about 10 cm. The system is based on measurements of acoustic signals between fixed seabed emitters and receiving hydrophones. A subset of the required acoustic beacons is powered by an autonomous power supply system based on a high-charge battery pack. This paper describes the innovative design used to build the battery packs, derived from the expertise in the construction of underwater detectors encapsulated in glass vessels. The battery pack uses a pressure resistant 17-inch glass sphere as housing, which contains a cluster of 96 batteries properly connected to supply an output DC voltage of 12 V with a total capacity of 410 Ah. The cluster of batteries is surrounded by silicone glue, that stacks all the part together, ensuring mechanical connection with the housing and protecting the batteries against humidity. In order to increase the operating time of the beacon, a custom designed wake-up board is added to implement a duty cycle operating mode. An electronic switch controlled by an ARDUINO microprocessor connects the battery pack to the beacon only for a defined time. So far, 8 supply systems have been deployed at the KM3NeT sites. The beacon battery pack could be easily modified for multipurpose deep-sea applications.